2018
DOI: 10.1016/j.ejvs.2017.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Arterial Calcification: The Role of Matrix Vesicles

Abstract: Vascular calcification is related to vascular diseases, for example, atherosclerosis, and its comorbidities, such as diabetes and chronic kidney disease. In each condition, a distinctive histological pattern can be recognised that may influence technical choices, possible intra-operative complications, and procedure outcomes, no matter if the intervention is performed by open or endovascular means. This review considers the classification and initiating mechanisms of vascular calcification. Dystrophic and meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
56
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 38 publications
1
56
0
3
Order By: Relevance
“…In VC, Fet-A is an inhibitor of calcification, which acts by protecting cells from crystal growth or deposition [257]. In this context, Fet-A is considered an important regulator of both bone resorption and VC.…”
Section: Fetuin-a (Fet-a)mentioning
confidence: 99%
“…In VC, Fet-A is an inhibitor of calcification, which acts by protecting cells from crystal growth or deposition [257]. In this context, Fet-A is considered an important regulator of both bone resorption and VC.…”
Section: Fetuin-a (Fet-a)mentioning
confidence: 99%
“…In fact, apoptosis occurs in VSMCs before the onset of calcification and VSMC "blebs" or apoptotic bodies probably concentrate calcium in a crystallized form [41]. Increasing evidence also show that VSMCs undergoing osteogenic transformation promote calcification by releasing matrix vesicles capable of nucleating hydroxyapatite [42]. Zhang et al [43] demonstrated that Sp1 gene silencing delayed vascular calcification by inhibiting the processes of phenotype switch, apoptosis and matrix vesicle release in VMSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular vascular calcification mechanisms are a complex intersection of regulatory pathways, including adenosine signaling, osteochondrogenesis, inflammation, endocrine pathways, hypoxia, malnutrition, autophagy, phosphate transport, and phosphate signaling. Please see these recent reviews for current detail on cardiovascular calcification mechanisms (Wu et al, 2013 ; Hortells et al, 2018 ; Zazzeroni et al, 2018 ).…”
Section: Calcific Potential Of the Placentamentioning
confidence: 99%